Pathogenic Bacteria on Musca domestica: Identification and Antibiotic Sensitivity via MALDI-TOF - Maria Kanan; Herawati Herawati; Inda Hafid; Sandy N. Sakati; Muhammad Syahrir (Journal of Public Health and Pharmacy, 2025)
Introduction: Flies are mechanical vectors that can transmit a variety of pathogenic bacteria, potentially causing human infections, especially in hospital settings. Rapid and accurate identification of these pathogenic bacteria, as well as assessment of their sensitivity to antibiotics, is essential for effective infection control. Methods: Sampling of flies in temporary rubbish bins in the hospital environment. Isolation of pathogenic bacteria from fly body surface by culture method, identification of bacteria using MALDI-TOF Mass Spectrometry technology. Antibiotic sensitivity test was conducted using Viteks 2 Compact to assess the effectiveness of therapy against the isolated bacteria. Ethical approval was obtained from Hasanuddin University Makassar. Results: Four species of pathogenic bacteria, namely Staphylococcus sciuri, Staphylococcus xylosus, Klebsiella pneumoniae, and Proteus mirabilis, were successfully identified quickly and accurately using the MALDI-TOF Mass Spectrometry method. Staphylococcus sciuri and Staphylococcus xylosus are sensitive to Benzylpenicillin, Oxacillin, and Ciprofloxacin, although Staphylococcus sciuri shows moderate resistance to Moxifloxacin. Klebsiella pneumoniae is resistant to Ampicillin, but is effective when combined with Sulbactam, while Proteus mirabilis is generally sensitive, except for Tigecycline. These findings are relevant for infection prevention strategies in hospitals, providing more appropriate antibiotic use guidance and supporting antimicrobial resistance control programs. Conclusion: MALDI-TOF Mass Spectrometry method proved effective in the rapid and accurate identification of pathogenic bacteria from flies. Antibiotic sensitivity testing is essential to determine the most effective therapy and avoid the use of less effective antibiotics.